Learning Microsoft Azure a Hands-On Training - Saini, Vijay (Packt Publishing, 2020)
Get a firm grip on Microsoft Azure through real-world exercises About This Video Build a solid foundation of cloud concepts and Azure architectural components Learn through Azure real-world example to clear Az-900 exam Explore real-world small projects and practice labs In Detail The primary reason for Microsoft Azure's immense popularity is that it supports a wide range of operating systems, tools, databases, programming languages, and, devices. This course starts off by introducing to you the Microsoft's platform for the cloud. You will then explore Azure web services and storage. In the concluding sections, you will deploy a Windows Azure cloud service and implement advanced cloud service functionalities. By the end of this course, you'll be become skilled enough to confidently operate Microsoft Azure to achieve business objectives. This course can be taken by absolute beginners including candidates with non-technical backgrounds, such as those involved in selling or purchasing cloud-based solutions and services, or who have some involvement with cloud-based solutions and services, as well as those with a technical background who want to brush up their fundamentals around cloud services and Azure.